OMNIBUS LAW CIPTA KERJA IN POLITICAL DISCOURSE AND PUBLIC OPINION - Sabarudin, Didin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The government decided that the omnibus law technique was a new legal breakthrough as an option to accomodate various overlapping multi-sector regulations. Law 11 of 2020 is projected to accelerate economic growth and increase the nation’s competitiveness by opening up the widest possible space for facilitating the business and investment climate to face the competition in the digital ecosystem of the world economy and global governance. This regulation raises debate in the public sphere, because this is suspected that the political process that occured during the legislative stages was formally flawed without the involvement of public participation. The dilemma between the policy agenda and the public agenda then continous through the communication media. This study aims to reveal the phenomenon of public opinion about the omni bus law of job creation and public participation in determining public affairs with multi-sectoral dimensions. Public opinion in the public sphere shows of the process of political communication that occurs as well as interaction between the policy agenda and the public agenda. The theoritical paradigm of phenomenology and research is critical in constructing an analytical descriptive approach with qualitative methods used to determine the relationship between the policy agenda, media agenda, and public agenda with various influencing factors.